Ameliorative Synergistic Effect of Honey and MO on Lead-Induced Alteration of Biochemical and Haematological Indices in Clarias gariepinus - Tolulope Ayandiran; Adebola Akintola; Busuyi David Kehinde; Ogundola Adijat; Fawole Olatunde; Akwu Bala Peter; Akitunde Akinniyi; Folorunso Kolade (Indonesian Food and Nutrition Progress, 2022)
Lead confers deleterious damage to the cells and it is necessary to explore further and develop a more effective way to ameliorate lead toxicity. This study aims to investigate how honey and Moringa oleifera (MO) can synergistically provide a more effective way to ameliorate lead toxicity. Groups of ten fish (Clarias gariepinus) were given Pb (0.30 g) and supplemented feed (T1) containing both honey (5 g) and MO (5 g). Others received pb (0.30 g) and supplemented feed (T2) containing either honey (10 g) or (T3) containing MO (10 g). Finally, hematological and biochemical analysis were conducted and a decline in the hematological parameters was observed. Also, the level of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), urea, creatinine, and malondialdehyde (MDA) significantly increased while glutathione (GSH) and superoxide dismutase (SOD) reduced in the group given lead only. However, these biochemical indices and hematological parameters are greatly restored in the group that received both honey and MO compared to the group that received either honey or MO. The findings of this study reveal that co-administration of both honey and MO synergistically damages caused by lead-induced toxicity better.